Implementasi Permainan Tradisional di Era Digital dan Integrasinya dalam Pendidikan Anak Usia Dini - Fitri Febri Handayani; Erni Munastiwi (UIR PRESS, 2022)
One of the nation's heritages that should always be preserved is traditional games, but in today's digital era, traditional games are less popular with children, some even don't know what traditional games are. The purpose of this study was to determine the implementation of traditional games in the digital era and their integration in early childhood education. The research site is in RA Al-Fayunasra, Danau Pulai Indah Village, Kempas District. The subjects in this study were the principal, 4 teachers consisting of 2 class teachers and 2 core teachers, students who stood from Group A and Group B, totaling 21 children. The research method uses descriptive qualitative methods. Data collection techniques using observation, interviews and documentation. Analyzed using the Miles & Huberman technique, the validity of the data using data triangulation. The results of the study show that the implementation of traditional games at RA Al-Fayunasra is integrated in two forms, namely during the learning process and when children are resting/playing and waiting to be picked up. During the learning process, traditional games are used as opening activities, namely the domikado game and the big circle and small circle. When the core activities of the game applied were hompimpa and uset games. Based on the results obtained, it can be concluded that the implementation of traditional games in early childhood education can be integrated both in the learning process and when children are outside the classroom.